2014
DOI: 10.2109/jcersj2.122.141
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of CeO<sub>2</sub> nanoparticles on photo-induced oxidative damage of DNA

Abstract: The present paper demonstrates that inorganic ceria (CeO 2 ) nanoparticles effectively inhibit anomalous oxidative damage of DNA induced by ultraviolet (UV) light irradiation. To utilize the CeO 2 nanoparticles for the protection test of DNA, a colloidal solution of monodispersed and crystallized CeO 2 nanoparticles is synthesized through a photochemical reaction of Ce(NO 3 ) 3 solution, followed by dialysis to remove unreacted electrolytes. Subsequently, the UV light induced oxidative damage of DNA in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For instance, zholobak et al [15] reported that CNPs prevented the decrease in cell viability of mouse fibroblasts (L929) and fibroblast-like cells of African Green monkey (VERO) exposed to UV. Fujita and Kamada [16] demonstrated that CNPs decreased oxidized DNA under UV light. Zholobak et al [17] reported that panthenol-stabilized CNPs protect human epidermoid cancer cells (Hep-2) and the diploid epithelial swine testicular cell line (ST-cells) from ROS and UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, zholobak et al [15] reported that CNPs prevented the decrease in cell viability of mouse fibroblasts (L929) and fibroblast-like cells of African Green monkey (VERO) exposed to UV. Fujita and Kamada [16] demonstrated that CNPs decreased oxidized DNA under UV light. Zholobak et al [17] reported that panthenol-stabilized CNPs protect human epidermoid cancer cells (Hep-2) and the diploid epithelial swine testicular cell line (ST-cells) from ROS and UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…NCD and water-soluble unmodified C60 fullerene exhibit radioprotective properties and can strongly reduce the harmful effects of ionizing radiation 16,17 . Cerium dioxide nanoparticles also have a photoprotective effect to the cells against ultraviolet light 18,19 . There are some reported data that nanoparticles of unmodified C60 fullerene protect skeletal muscles from ischemic lesions 20,21 , have a stabilizing effect on ISSN: 2250-1177 [2] CODEN (USA): JDDTAO enzymes, protecting them from thermal and oxidative inactivation 22 .…”
Section: Introductionmentioning
confidence: 99%